Cracking up : black feminist comedy in the twentieth and twenty-first century United States - Wood, Katelyn Hale, 1975- (Studies in theatre history and culture., 2021)
"Cracking Up archives and analyzes Black feminist stand-up comedy in the United States over the past sixty years. Looking closely at the work of Jackie "Moms" Mabley, Mo'Nique, Wanda Sykes, Sasheer Zamata, Sam Jay, Phoebe Robinson, Jessica Williams, and Michelle Buteau, this book shows how Black feminist comedy and the laughter it ignites are vital components of feminist, queer, and anti-racist protest. Cracking Up frames theatre and live performance as an important platform from which to examine citizenship in the United States, articulate Black feminist political thought, and subvert structures of power. Author Katelyn Hale Wood interprets these artists not as tokens in their white/male dominated field, but as part of a continuous history of Black feminist performance and presence in the United States. Broadly, the book also champions comedic performance and theatre history as imperative contexts for advancing historical studies of race, gender, and sexuality. From the comedy routines popular on Black vaudeville circuits to stand-up on contemporary social media platforms, Cracking Up excavates an overlooked history of Black women who made the art of joke-telling a key part of radical performance and political engagement"--